Fetal therapies as standard prenatal care in Japan - Haruhiko Sago; Seiji Wada (Obstetrics & Gynecology Science, 2020)
With recent advances in fetal medicine, various attempts have been made to save fetuses facing perinatal death or devastating consequences despite optimal management after birth. The concept of the fetus as a patient has been established through the application of in utero treatments. This paper reviews fetal therapies in order to highlight the role of perinatal medicine as standard prenatal care. Fetal therapies consist of medical therapy, percutaneous ultrasound-guided surgery, fetoscopic surgery, and open fetal surgery. In the 1980s, with advances in ultrasound imaging, percutaneous ultrasound-guided surgeries such as vesicoamniotic shunting for lower urinary tract obstruction and thoracoamniotic shunting (TAS) for fetal hydrothorax (FHT) were started. In the 1990s, fetoscopic laser surgery (FLS) for twin-twin transfusion syndrome (TTTS) was introduced, and later, a fetoscopic approach for congenital diaphragmatic hernia was also established. The revival of open fetal surgery, introduced in the 1980s by pediatric surgeons, began in the 2010s after a successful clinical study for myelomeningocele. Although many fetal therapies are still considered experimental, some have proven effective, such as FLS for TTTS, TAS for primary FHT, and radiofrequency ablation (RFA) for twin reversed arterial perfusion (TRAP) sequence. These three fetal therapies have been approved for coverage by Japan National Health Insurance as a result of clinical studies performed in Japan. FLS for TTTS, TAS for primary FHT, and RFA for TRAP sequence have become standard prenatal care approaches in Japan. These three minimally invasive fetal therapies will help improve the perinatal outcomes of fetuses with these disorders.